PENGARUH KOMPETENSI DAN INSENTIF TERHADAP PRESTASI KERJA GURU SMK SINAR PANCASILA BALIKPAPAN KALIMANTAN TIMUR - jurnalpps pps; C. Sri Hartati; Woro Utari; Suroso Suroso (Prodi Magister Manajemen Universitas Wijaya Putra, 2022)
This study aims to examine and explain the effect of competence and incentives on teacher work performance at SMK Sinar Pancasila Balikpapan, East Kalimantan. This type of research is an explanatory research with a quantitative approach. The population in this study were all 36 teachers of SMK Sinar Pancasila Balikpapan. The entire population was used as the research sample or respondents because there were less than 100 people. The results of the study show that teacher competence has a significant effect on teacher work performance at SMK Sinar Pancasila Balikpapan. Then teacher incentives have a significant effect on the work performance of SMK Sinar Pancasila Balikpapan teachers and stimulant competencies and incentives have a significant effect on teacher work performance at SMK Sinar Pancasila Balikpapan.